House of many ways - Jones, Diana Wynne (New York : Greenwillow Books, 2008)
When Charmain is asked to housesit for Great Uncle William, the Royal Wizard of Norland, she is ecstatic to get away from her parents, but finds that his house is much more than it seems.
Keywords: Housesitting -- Fiction; Fantasy fiction